(untitled) (The Pakistan Development Review, 2017)
This paper empirically analyses the impact of institutions, both formal and informal, on innovation performance of sampled countries at different stages of development. Data of 72 sampled countries on Research and Development Expenditures, numbers of article published, human capital, trade openness, internet users are collected from United Nations Educational, Scientific and Cultural Organisation (UNESCO), International Country Risk Guide (ICRG) and World Bank database. Formal and informal institutions indexes are constructed using data from Country Risk Guide and The World Value Survey (WVS). Fixed effect and System GMM technique are used to estimate the dynamic relationship between innovation performance and institutional indexes. The study finds positive significant effect of institutions on innovation in case of aggregate sample of developed and developing countries. However, the effects of formal institutions are more significant in case of sample of developed countries, while in developing countries informal institutions are found more effective than formal institutions in affecting innovation performance. The results also show that both formal and informal institutions are supplementary to each other in case of developing countries. Therefore, it is suggested that focus should be given to informal institutions. Moreover, collective initiatives be encourage in developing countries to have diverse ideas from different sectors of the countries. In addition, developing countries should initiate collaborative research projects with technologically advanced countries research and education institutions so as to learn from each other’s ideas and experiences. Keywords: Formal Institutions, Informal Institutions, Innovation